Interaction between old settlement areas and natural vegetation - Baylak, Halil Mesut (Technium Social Sciences Journal, 2024)
Areas that have been considered as cultural environments since ancient times have been under the influence of anthropogenic activities. That's why vegetation; It has been destroyed as a result of field clearing, grazing, fire, cutting and recently increasing mining activities. Studies carried out to reduce the impact of destruction may cause the vegetation to diversify or the presence of alien species in the field. Studies conducted in these areas, especially pollen analyses, reveal the vegetation transformation that the areas have undergone. In order to reveal the causes, results and interaction of these transformations, the results of the study were shared as a result of the research in the sample of the Gökyurt (Kilistra) ancient settlement area and its surroundings, located within the borders of Meram district of Konya province. In order to achieve the aim of the study, studies on the vegetation characteristics of the field were evaluated and the vegetation map of the field was prepared and the evaluations in the conclusion were reached.